2015
DOI: 10.1088/1758-5090/7/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of compositionally and topographically complex robust tissue forms by 3D-electrochemical compaction of collagen

Abstract: Collagen solutions are phase-transformed to mechanically robust shell structures with curviplanar topographies using electrochemically induced pH gradients. The process enables rapid layer-by-layer deposition of collagen-rich mixtures over the entire field simultaneously to obtain compositionally diverse multilayered structures. In-plane tensile strength and modulus of the electrocompacted collagen sheet samples were 5200 -fold and 2300 -fold greater than that of uncompacted collagen samples. Out of plane comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…To the best of our knowledge, load-bearing growth factor conjugated pure collagen sutures have not been used for repair of lacerated tendons. Our group has developed electrochemical compaction and alignment of collagen molecules as a powerful method to obtain load-bearing collagen threads [25-28]. Such compaction and alignment has also been shown to induce tenogenic differentiation of mesenchymal stem cells [25, 29].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, load-bearing growth factor conjugated pure collagen sutures have not been used for repair of lacerated tendons. Our group has developed electrochemical compaction and alignment of collagen molecules as a powerful method to obtain load-bearing collagen threads [25-28]. Such compaction and alignment has also been shown to induce tenogenic differentiation of mesenchymal stem cells [25, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen sheet was fabricated in sheet form by electrocompaction method described before 20, 23 . Briefly, a 30×10×1.5 mm rectangular window was cut in a plastic piece.…”
Section: Methodsmentioning
confidence: 99%
“…Electrocompaction of collagen in the sheet form was carried out as described before . Briefly, a rectangular window of 30 × 10 × 1.5 mm was cut in a plastic piece.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge there is no study which introduces SA directly to the pure collagen substrate by incorporating different stiffness values in different material directions and studies the effect on cytoskeletal response and differentiation toward anisotropic tissue lineage. Our research group demonstrated transformation of monomeric collagen solutions to solid phase by electrochemical gradients induced by linear electrodes . The method generates highly dense and aligned collagen threads with a packing density (1030 mg mL −1 ) one of the highest reported to date .…”
Section: Introductionmentioning
confidence: 99%